Hypertension in the elderly - Głuszek, Jerzy (Przewodnik Lekarza/Guide for GPs, 2006)
Prevalence of arterial hypertension increases with age and causes higher risk of cardio-vascular complications. The elderly should be treated to the same goal (<140/90 mmHg) as younger patients, although a more gradual reduction in blood pressure to this level should be recommended and patients should be carefully observed and questioned for side effects. In the presence of comorbidities (ischemic heart disease or after stroke) an intermediate goal of systolic blood pressure (<160 mmHg) may be advisable. Intervention should include salt restriction. In the elderly all antihypertensive drugs may be used in treatment of hypertension but the choice of antihypertensive agents depends on comorbid diseases.